Synchronous Motor Design and Analysing the Output Characteristics - Riza, Mior Ahmad Faiz (2008)
AC Synchronous Motors range in size from sub-fractional horsepower to over 10,000 horsepower. Smaller synchronous motors can be found in household devices such as clocks, timers, fans and cassette players, and as stepper motors in computer disk drives and printers. Larger synchronous motors are used in process industries and drive equipment such as compressors. Large synchronous motors most commonly employ a three-phase system. The smaller AC Synchronous Motors commonly use a single-phase system. Synchronous motor is consists of two parts those are stator and rotor. Stator is stationary part that produces rotating magnetic field and then, the rotor locks into step with rotating magnetic field. This paper focuses on uses the permanent magnet on rotor shaft to produce magnetic field instead of uses slip rings and carbon brush to supply external dc source to the shaft. Permanent magnet synchronous motor is also called brushless because the excitation flux is produced by permanent magnet. Application of neodymium-iron-boron (Nd2Fe14B) and samarium cobalt (Sm1Co5 and Sm2Co17) rare earth magnets results in high torque and power density, efficiency, and controllability, reliability, and ruggedness. The synchronous motor has the same physical stator as induction motor. Then the output of two type of motor can be analyse and compared the result. The output that should be considered is frequency, rpm, torque, hp, losses, and efficiency. From this project we can use the spec of induction motor to guide in design basic principal of synchronous motor with the same spec. Through of this some of development should be done to improve the efficiency and reliability of the motor.